2023
DOI: 10.21203/rs.3.rs-2786755/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enacted Phronesis (Practical Wisdom) in Medical Practitioners: An Empirical Mixed Methods Study

Abstract: Background Phronesis (Practical Wisdom) is a useful way of conceptualising professional knowledge in the field of Medicine. Phronesis is one of five intellectual virtues described by Aristotle. Two of these intellectual virtues are well embedded in Medical Education; scientific knowledge (episteme) and technical skill (techne). The remaining two intellectual virtues are philosophical wisdom (sophia) and intellectual insight (nous). A critical interpretive literature review identified a lack of empirical work o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
1
0
0
Order By: Relevance
“…This dependence is illustrated, for instance, when it is suggested that those who demonstrate practical wisdom need to be just so they can see the proper claims of others, temperate so that their vision is not clouded by the pleasures or distractions of the moment, and courageous so that they will persist in what they see as good even when it does not work to their personal benefit 60 . Such observations conform with empirical evidence that associates multiple virtues with wise decision making in medicine 30,61 and with claims about the way good professional judgement in medicine depends on additional traits, such as the courage, diligence and curiosity needed to navigate ambiguous and uncertain situations 62 . More generally, our results confirm what typical lists of virtues relevant to medicine imply, that practical wisdom is one of many character traits physicians need to excel as health professionals 3,51,56,63–66 .…”
Section: Discussionsupporting
confidence: 88%
“…This dependence is illustrated, for instance, when it is suggested that those who demonstrate practical wisdom need to be just so they can see the proper claims of others, temperate so that their vision is not clouded by the pleasures or distractions of the moment, and courageous so that they will persist in what they see as good even when it does not work to their personal benefit 60 . Such observations conform with empirical evidence that associates multiple virtues with wise decision making in medicine 30,61 and with claims about the way good professional judgement in medicine depends on additional traits, such as the courage, diligence and curiosity needed to navigate ambiguous and uncertain situations 62 . More generally, our results confirm what typical lists of virtues relevant to medicine imply, that practical wisdom is one of many character traits physicians need to excel as health professionals 3,51,56,63–66 .…”
Section: Discussionsupporting
confidence: 88%